Social movement unionism or professionalism? the union movement of Taiwanese documentary makers. (1st October 2010) - ,
Abstract : Taiwanese documentaries have grown rapidly in terms of local consumption and production since the 2000s, despite the dominance of Hollywood in the local film market. However, most documentary workers still suffer from poor working conditions because of a lack of sufficient resources for local productions. In response to this situation, Taiwanese documentary makers founded a labour union in 2006 to protect their basic working rights. This paper describes this union movement as well as analysing the challenges that it encounters. These challenges include a very low degree of participation in unions among Taiwanese cultural workers, anti-union sentiment among professionals and freelancers and the ''association-prone'', as opposed to ''union-prone'' nature of Taiwanese occupational unions. Despite these obstacles, the strong traditional linkages between Taiwanese documentary-makers and dissenting social and political movements has enabled the documentary workers' union to pursue a form of ''social movement unionism'', which opens up opportunities for revitalisation even when there is a general decline of the trade union movement.